2020
DOI: 10.1136/jnnp-2020-323822
|View full text |Cite
|
Sign up to set email alerts
|

Nusinersen safety and effects on motor function in adult spinal muscular atrophy type 2 and 3

Abstract: ObjectiveTo retrospectively investigate safety and efficacy of nusinersen in a large cohort of adult Italian patients with spinal muscular atrophy (SMA).MethodsInclusion criteria were: (1) clinical and molecular diagnosis of SMA2 or SMA3; (2) nusinersen treatment started in adult age (>18 years); (3) clinical data available at least at baseline (T0-beginning of treatment) and 6 months (T6).ResultsWe included 116 patients (13 SMA2 and 103 SMA3) with median age at first administration of 34 years (range 18–72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
150
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 32 publications
15
150
3
5
Order By: Relevance
“…Even though SMA is generally described as a symmetric disorder, it is not uncommon to see asymmetrical weakness: Kang et al (46) reported three female type 3 SMA patients with asymmetrical weakness, showing also upper motor neuron signs that have always been absent in our patient. Despite the small sample size considered here and the relatively short observation period, our results are in line with those reported by the German and Italian studies (47,48). It should also be noted that all patients reported some further improvement in motor function, which could not be captured by their repeated functional scores possibly because of the discrete nature of such scales.…”
Section: Clinical Datasupporting
confidence: 91%
“…Even though SMA is generally described as a symmetric disorder, it is not uncommon to see asymmetrical weakness: Kang et al (46) reported three female type 3 SMA patients with asymmetrical weakness, showing also upper motor neuron signs that have always been absent in our patient. Despite the small sample size considered here and the relatively short observation period, our results are in line with those reported by the German and Italian studies (47,48). It should also be noted that all patients reported some further improvement in motor function, which could not be captured by their repeated functional scores possibly because of the discrete nature of such scales.…”
Section: Clinical Datasupporting
confidence: 91%
“…Similarly, the study by Maggi et al reported a mean change among SMA type 3 walkers in the HFMSE was 2.38 ± 2.71 (median 2, range −3 to 8) in 40 subjects at 10 months and 2.37 ± 2.22 (median 2, range −2 to 6) in 27 subjects at 14 months (17). The percent increase in HFMSE of ≥3 points was 43 and 48% after 10 and 14 months of treatment (17). In our study, the impact of nusinersen on the 6MWT was less robust as compared with the studies by Hagenacker et al (11) and Maggi et al (17) 17).…”
Section: Impact Of Nusinersen On Secondary Outcome Measuresmentioning
confidence: 58%
“…Nusinersen was approved for all types of SMA, but approval was primarily based on evidence in infants and children ages 2-15 (7)(8)(9). There is emerging data supporting the use of nusinersen in adults with SMA (10)(11)(12)(13)(14)(15)(16)(17). However, there is a limited understanding of how delayed or late SMN restoration may result in improved function.…”
Section: Introductionmentioning
confidence: 99%
“…Sansone et al recently recommended OM in adult SMA based upon expert opinion of international neuromuscular experts [13] and their results align with the findings of the present study, with differences only in the selection of the SMAFRS and the TUG. Similarly, Hagenacker et al, Walter et al and Maggi et al studied the effects of nusinersen (an SMN2-targeted anti-sense oligonucleotide [6]) in an adult SMA population and all utilized the HFMSE, RULM, and 6MWT [25][26][27] in evaluation of therapy effectiveness and safety. In 2016, Mercuri et al selected the HFMSE as the primary outcome measure when reporting upon the natural progression of SMA in children and adults [28].…”
Section: Discussionmentioning
confidence: 99%